Tao nō̜i ʻō̜ngkham : nithān phư̄a kānrīanrū phāsā Lānnā - Natthaphong Pančhaburī (Samnak Songsœ̄m Sinlapa Watthanatham, Mahāwitthayālai Chīang Mai, 2014)
Northern Thai language reader through a folktale.